2020
DOI: 10.1177/2050312120932706
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital point-of-care ultrasound: A transformative technology

Abstract: Point-of-care ultrasound at the bedside has evolved into an essential component of emergency patient care. Current evidence supports its use across a wide spectrum of medical and traumatic diseases in a variety of settings. The prehospital use of ultrasound has evolved from a niche technology to impending widespread adoption across emergency medical services systems internationally. Recent technological advances and a growing evidence base support this trend. However, concerns regarding feasibility, education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
(68 reference statements)
0
27
0
3
Order By: Relevance
“…The use of POCUS to augment the work of paramedics and first responders has been previously explored, but the size, cost, and necessity for multiple probes inherent to standard machines significantly limited the ability to undertake large scale prehospital studies [ 48 ]. With the advent of HHU devices, research on prehospital POCUS and its effect on patient outcomes is now feasible [ 49 ]. The cost and portability of HHU devices make them ideal diagnostic tools for first responders as well as EPs who staff large-scale events, sometimes in areas with few existing medical resources [ 4 ].…”
Section: Current Use Of Hhus In the Edmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of POCUS to augment the work of paramedics and first responders has been previously explored, but the size, cost, and necessity for multiple probes inherent to standard machines significantly limited the ability to undertake large scale prehospital studies [ 48 ]. With the advent of HHU devices, research on prehospital POCUS and its effect on patient outcomes is now feasible [ 49 ]. The cost and portability of HHU devices make them ideal diagnostic tools for first responders as well as EPs who staff large-scale events, sometimes in areas with few existing medical resources [ 4 ].…”
Section: Current Use Of Hhus In the Edmentioning
confidence: 99%
“…Their high portability and ability to provide real-time diagnostics make these devices ideal for such circumstances [ 4 ]. Similarly, HHU is proving invaluable to practitioners in austere environments that otherwise have no reliable imaging source [ 3 , 4 , 15 , 49 ]. Burleson et al retrospectively reported the experience of ultrasound-trained physicians using the Butterfly iQ HHU in an austere East African ED [ 8 ].…”
Section: Current Use Of Hhus In the Edmentioning
confidence: 99%
“…cold, warm, dark, sunny, rain, snow). The evidence for non-physician performed thoracic ultrasound examinations differ regarding feasibility, quality, and accuracy and it is still debated if and how prehospital thoracic ultrasound should be implemented [14][15][16]. Only a few minor published studies explore the feasibility and accuracy of these ultrasound examinations.…”
Section: Introductionmentioning
confidence: 99%
“…POCUS seems to be accepted and available in Europe. Besides the more frequent use of POCUS compared with North America, the survey underlines that HEMS in Europe is mainly physician staffed which can explain the frequent use of POCUS (9,28). Some participants stated that POCUS is used in more than 30% of their patients indicating proper training in a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…European HEMS organizations should agree on common POCUS curriculum with an accepted standard that suits their needs. Competency is a key factor in successful clinical applications [4,28]. Using a Delphi methodology, Micheller et al de ned a total of ve modalities (cardiac, thoracic, FAST, aorta, and procedural), with 32 measured competencies and 72 sub competencies [29] as the basis for the needed curriculum.…”
Section: Discussionmentioning
confidence: 99%